Characterization of Fusobacterium isolates from the respiratory tract of white-tailed deer (Odocoileus virginianus) - Brooks, Jason W.; Kumar, Amit; Narayanan, Sanjeev K.; Myers, Suzanne; Brown, Kayla; Nagaraja, Tiruvoor G.; Jayarao, Bhushan M. (My University, 2014)
A total of 23 clinical isolates of Fusobacterium spp. were recovered at necropsy over a 2-year period from the respiratory tract of white-tailed deer (Odocoileus virginianus). Isolates were identified as Fusobacterium varium (18/23), Fusobacterium necrophorum subsp. funduliforme (3/23), and Fusobacterium necrophorum subsp. necrophorum (2/23). Using polymerase chain reaction–based detection of virulence genes, all F. necrophorum isolates were positive for the promoter region of the leukotoxin operon and the hemagglutinin-related protein gene, while all F. varium isolates were negative. The presence of the leukotoxin gene in F. necrophorum isolates and the absence of this gene in F. varium isolates were confirmed by Southern hybridization using 2 separate probes. Toxicity to bovine polymorphonuclear leukocytes was observed with all F. necrophorum isolates, but was not observed in any F. varium isolates. Susceptibility to antimicrobials was markedly different for F. varium as compared to F. necrophorum. In summary, no evidence of leukotoxin production was detected in any of the 23 F. varium isolates used in the current study. The data suggests that F. varium, the most common species isolated, may be a significant pathogen in deer with a different virulence mechanism than F. necrophorum.
Keywords: Fusobacterium necrophorum; Fusobacterium varium; Leukotoxin; White-tailed deer